Layanan Konseling Individual untuk Mengatasi Kesulitan Belajar Siswa - Wahyuningsih, Siti; Wahyuni, Wahyuni (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2020)
Learning difficulties are a condition of the learning process that is characterized by certain obstacles to achieving learning outcomes, so the conditions where students cannot learn as they should. this research was conducted in class VII A Mts Al Ma'arif Wuluhan, this type of research was quantitative by using the PTBK approach with one-by-one design or face to face. the population in this study were all students of class VII A Mts Al Ma'arif Wuluhan with sampling taken using purposive sampling. The data collection technique in this study was using observations and items distributed then analyzed by the method of action of the standard model. Learning difficulties of students at the VII A grade MTS AL MA'ARIF school, this is true as evidenced by the large percentage of students learning difficulties before being given 28%, after being given action through two large cycles the percentage decreased to 14% the level of learning difficulties of students from 21 students.